Drug-induced (toxic) glaucoma (Canadian Eye Care Today, 2022)
Glaucoma is the leading cause of irreversible blindness in the world and the second most common cause of blindness overall. The prevalence of glaucoma is approximately 3% of the population worldwide. Due to the fact that increasing age is a risk factor for the development of glaucoma, an increase in life expectancy worldwide will be associated with a predicted increase in the prevalence of glaucoma. Similarly, advancements in medicine and an aging population have led to an increase in polypharmacy. Nearly two-thirds of all US adults aged 40–64 and 90% of individuals ≥ 65 years of age have been prescribed 5 or more medications at a time. Unfortunately, when assessing glaucoma patients, physicians may overlook systemic medications and focus solely on the topical medications. However, many systemic drugs have been shown to cause or worsen glaucoma. Therefore, the rise in polypharmacy and its effect on glaucoma must be better understood in order to decrease the worldwide glaucoma burden. Drug-induced glaucoma, or toxic glaucoma, is a form of secondary glaucoma that can be distinguished by the mechanism causing the glaucoma: open angle or closed angle glaucoma. The overall incidence of drug-induced glaucoma is unknown.